2008
DOI: 10.1145/1344418.1344424
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable content-based router using hardware-accelerated language parser

Abstract: This article presents a dense logic design for matching multiple regular expressions with a field programmable gate array (FPGA) at 10+ Gbps. It leverages on the design techniques that enforce the shortest critical path on most FPGA architectures while optimizing the circuit size. The architecture is capable of supporting a maximum throughput of 12.90 Gbps on a Xilinx Virtex 4 LX200 and its performance is linearly scalable with size. Additionally, this article presents techniques for parsing data streams to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For instance, in [Lunteren et al 2004;Dai et al 2010], a specific architecture was proposed to speed-up the eXtensible Markup Language (XML) document parsing. Similarly, in [Moscola et al 2008], an FPGA based regular expression language is used to parse XML based streams. These works have demonstrated that FPGAs offer a viable alternative thanks to their power efficiency as well as their higher throughput when compared with software implementation.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, in [Lunteren et al 2004;Dai et al 2010], a specific architecture was proposed to speed-up the eXtensible Markup Language (XML) document parsing. Similarly, in [Moscola et al 2008], an FPGA based regular expression language is used to parse XML based streams. These works have demonstrated that FPGAs offer a viable alternative thanks to their power efficiency as well as their higher throughput when compared with software implementation.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, high-level specifications of network protocol messages are mapped directly into hardware description languages such as VHDL to be then successively synthesized into ASIC or FPGA [17,18,19]. However, hardware parsers are provided as is and require strong understanding of hardware design fundamentals to integrate them with network programming applications.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, high-level specifications of network protocol messages are mapped directly into hardware description languages such as VHDL to be then successively synthesized into ASIC or FPGA [12], [13], [14]. However, hardware parsers are provided as is and require strong understanding of hardware design fundamentals to integrate them with network programming applications.…”
Section: Related Workmentioning
confidence: 99%